Improvement of glucose production by raw starch degrading enzyme utilizing acid-treated sago starch as substrate - Marlida, Yetti; Saari, Nazamid; Karim, Roselina; Mohammed, Abdulkarim Sabo (Universiti Putra Malaysia Press, 2007)
The native sago starch exists as a compact crystalline structure and is not efficiently hydrolyzed by Raw Starch Degrading Enzyme (RSDE). In order to enhance its hydrolysability, the starch was treated with acid and heated below its gelatinization temperature, thus increasing the accessibility of the sago starch granule to enzymatic attack. Results showed that treatment of sago starch with acid at pH 2.0 and temperature 65oC for 2 hours greatly enhanced its conversion rate to glucose from 53.3% to 71.9%. It is clearly shown that high yield of glucose is produced during hydrolysis of acid-treated sago starch using the Raw Starch Degrading Enzyme from Acremonium sp. The difference between the acid-treated and untreated sago starch in this study could be due to the differences on the surface of the sago starch granule which may influence the accessibility and diffusion of enzyme into the starch during hydrolysis.